Development of 21st Century Learning Tools Through a Scientific Approach Based on HOTS and TPACK in Elementary Schools (Global Scientific Review, 2023)
The study aims to generate a 21st century learning device design (Lesson Plan, Teaching Material, and Learning Evaluation) through a scientific approach based on HOTS (Higher Order Thinking Skill) and PACK (technological pedagogical content knowledge) in elementary schools. At the same time, this present study applies a Research and Development method based on the development research model of Saputro, which adopts modifications from Borg and Gall and Sugiono, namely preliminary studies, model development/design, and testing. Meanwhile, this study is only up to the model design phase.